SARS-CoV-2, Trait Anxiety, and the Microbiome - Büttiker, Pascal; Weissenberger, Simon; Stefano, George B.; Kream, Richard M.; Ptacek, Radek (Frontiers in Psychiatry, 2021)
During the COVID-19 pandemic, research on the relationships between the virus and its human host has become fundamental to understand this pathology and its effects. Attaining this profound understanding is critical for the effective containment and treatment of infections caused by the virus. In this review, we present some possible mechanisms by which psychopathological symptoms emerge following viral infections of the central nervous system (CNS). These proposed mechanisms are based on microbial communication and the induced priming of microglial antibody activation within the CNS through Toll-like receptor signaling. In this process, chronic microglial activation causes increased glutamate release in virally-altered, high-density neuronal structures, thereby modulating cognitive networks and information integration processes. This modulation, in turn, we suggest, affects the accuracy of sensory integration and connectivity of major control networks, such as the default mode network. The chronic activation of immunological responses and neurochemical shifts toward an elevated glutamate/gamma-aminobutyric acid ratio lead to negative reinforcement learning and suboptimal organismic functioning, for example, maintaining the body in an anxious state, which can later become internalized as trait anxiety. Therefore, we hypothesize that the homeostatic relationship between host, microbiome, and virome, would be decisive in determining the efficiency of subsequent immunological responses, disease susceptibility, and long-term psychopathological effects of diseases that impact the CNS, such as the COVID-19.